A Scalable Platform for Functional Nanomaterials via Bubble‐Bursting. Issue 21 (23rd March 2016) - Feng, Jie; Nunes, Janine K.; Shin, Sangwoo; Yan, Jing; Kong, Yong Lin; Prud'homme, Robert K.; Arnaudov, Luben N.; Stoyanov, Simeon D.; Stone, Howard A.
Abstract : A continuous and scalable bubbling system to generate functional nanodroplets dispersed in a continuous phase is proposed. Scaling up of this system can be achieved by simply tuning the bubbling parameters. This new and versatile system is capable of encapsulating various functional nanomaterials to form functional nanoemulsions and nanoparticles in one step.